Influence of saliva on individual in-mouth aroma release from raw cabbage (Brassica oleracea var. capitata f. rubra L.) and links to perception. Issue 12 (December 2018) - Frank, Damian; Piyasiri, Udayasika; Archer, Nicholas; Jenifer, Jenifer; Appelqvist, Ingrid
Abstract: Raw or minimally processed vegetables are popular for health reasons and for their unique textural and flavor attributes. While many aroma volatiles are produced in situ when plant tissues are mechanically disrupted, enzymes expressed in bacteria in oral microbiota such as cysteine- β -lyase (EC 4.4.1.13) may also contribute to aroma formation in-mouth during consumption. Interactions between raw cabbage and fresh human saliva (n = 21) were measured ex vivo by real-time monitoring of sulfur volatile production by proton transfer reaction mass spectrometry (PTR-MS). Inter-individual differences in the concentration of sulfur volatiles from the breakdown of S -methyl-L-cysteine sulfoxide (SMCSO) in fresh cabbage by saliva were characterized and a 10-fold difference in the extent of sulfur volatile production was measured across individuals. The overall intensity and garlic odor of raw cabbage was positively correlated with the concentration of sulfur volatiles after incubation with fresh human saliva. A buildup of SMSCO-derived sulfur volatiles in vivo, over twenty repeated mouthfuls was demonstrated, indicating that these reactions can affect sensory perception within the timescale of eating. These findings show the perceived odor experienced when eating cabbage differs, thus resulting in a unique flavor experience between individuals.